The Passion of Work and Proactive Work Behavior: Validation of ‘New’ Protean Career Attitude Through Nomological Network - Nilawati, Levi; Kismono, Gugup; Handoko, Hani; Rosari, Reni (JDM (Jurnal Dinamika Manajemen), 2021)
Protean careers are understood and measured using different concepts. Apart from being confusing, it also causes divergences that result in limited operationalization of the protean career. O This study aims to develop a more comprehensive tool for measuring protean careers by examining the nomological network of ‘new’ protean career attitudes. Researchers added a measure of the affective component of love for work, in addition to dimensions driven by self-values and self-directed behavior. The results of the construct validity test through a nomological network involving 160 respondents showed two critical points. First, on the relationship between the dimensions, the dimensions of love for work and self-direction behavior are related to the harmonious passion variable and the proactive work behavior of career initiatives and personal initiatives. Second, the relationship within the dimension shows that the dimensions of love for work, driven by self-values, and self-directed behavior are interrelated. Additional validity tests, such as convergent, discriminant, and predictive validity tests, indicate that the question items are valid. Future research needs to pay more attention to the affective dimensions of love for work and harmonious passion.e.